Enhanced Charge Transport by Incorporating Formamidinium and Cesium Cations into Two‐Dimensional Perovskite Solar Cells. Issue 34 (11th July 2019) - Gao, Liguo; Zhang, Fei; Chen, Xihan; Xiao, Chuanxiao; Larson, Bryon W.; Dunfield, Sean P.; Berry, Joseph J.; Zhu, Kai
Abstract: Organic‐inorganic hybrid two‐dimensional (2D) perovskites ( n ≤5) have recently attracted significant attention because of their promising stability and optoelectronic properties. Normally, 2D perovskites contain a monocation [e.g., methylammonium (MA + ) or formamidinium (FA + )]. Reported here for the first time is the fabrication of 2D perovskites ( n =5) with mixed cations of MA +, FA +, and cesium (Cs + ). The use of these triple cations leads to the formation of a smooth, compact surface morphology with larger grain size and fewer grain boundaries compared to the conventional MA‐based counterpart. The resulting perovskite also exhibits longer carrier lifetime and higher conductivity in triple cation 2D perovskite solar cells (PSCs). The power conversion efficiency (PCE) of 2D PSCs with triple cations was enhanced by more than 80 % (from 7.80 to 14.23 %) compared to PSCs fabricated with a monocation. The PCE is also higher than that of PSCs based on binary cation (MA + ‐FA + or MA + ‐Cs + ) 2D structures. Abstract : Triple whammy : Reported here is the fabrication of 2D perovskites ( n =5) with triple cations. The resulting perovskites feature longer carrier lifetime, greater mobility, and higher conductivity. The efficiency of 2D perovskite solar cells (PSCs) with triple cations was enhanced by more than 80 % (from 7.80 to 14.23 %) compared to PSCs fabricated with a monocation. The efficiency is also higher than that of PSCs based on binary cation 2D structures.